电动执行机构的高效率传动设计 - 贺赟晖; 王成; 王威; 禹建勇 (Jixie chuandong)
Electric actuator should be self-locking when stop,therefore,the worm-drive is the major transmission mode.The worm-drive is the main factor of the efficiency loss in the electric actuator.The high efficiency design methods are given from the effects of speed and load by discussing the main factors of transmission efficiency.